1993
DOI: 10.1136/jcp.46.10.931
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus in normal, pre-malignant, and malignant lesions of the uterine cervix.

Abstract: Aim-To detect the presence or absence of Epstein-Barr virus (EBV) in cervical lesions ranging from normality to invasive malignancy. Methods EBV. In these, however, the evidence is less conclusive and the consistency of the association has yet to be established.Invasive carcinoma of the cervix is one of the commonest malignant tumours of the female genital tract. Much controversy surrounds its aetiology. The possibility of a sexually transmissible infectious carcinogen in the genesis of cervical neoplasia has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 11 publications
5
42
1
2
Order By: Relevance
“…These results are comparable with those published by Landers et al (15), who found that 8% of CIN 2 and CIN 3 samples tested positive for EBV DNA. Again, the presence of EBV DNA within the cervix raises the possibility that this virus may be sexually transmitted.…”
Section: Discussionsupporting
confidence: 82%
“…These results are comparable with those published by Landers et al (15), who found that 8% of CIN 2 and CIN 3 samples tested positive for EBV DNA. Again, the presence of EBV DNA within the cervix raises the possibility that this virus may be sexually transmitted.…”
Section: Discussionsupporting
confidence: 82%
“…These results concur with those found in a recent (18). A similar increase in prevalence of cervical EBV DNA shedding has been reported in other studies as well (11,12,26). Sasagawa et al evaluated EBV mRNA expression at the cervix and found that the EBV genes EBER-1, LMP-1, and EBNA-2 were expressed significantly more frequently in tissue samples from CIN and cancer patients than women with normal cervices (19).…”
Section: Discussionsupporting
confidence: 51%
“…Sixbey et al (13) have demonstrated that uterine cervical cells can be infected by EBV, following the findings of Landers et al (14), who found EBV in 43% of cervical cancer tissues, 8% of cervical intraepithelial neoplasias, and 0% of normal cervical tissues.…”
Section: Introductionmentioning
confidence: 99%